Avaliação das alterações cardiopulmonares precoces e tardias resultantes da secção da cadeia simpática realizada por videotoracoscopia em pacientes com hiperidrose - Lima, Juliana Ferreira de [UNESP] (2016)
The thoracoscopic sympathectomy is the most widely used treatment for patients with primary hyperhidrosis and the most discussed side effect is reflex sweating. However, chronotropic and late side effects are neglected and there is discrepancy findings in studies that evaluated it. Moreover, although currently recommended approach the third and fourth ganglia, all studies found in literature addressed the approach of the second and third ganglia. Objective: To assess cardiopulmonary performance in the immediate, mediate and late postoperative thoracoscopic sympathectomy period, as well as assess whether chain section to the levels of 3rd and 4th thoracic ganglia directly affects the performance on cardiopulmonary exercise testing, such as. Methods: Pulmonary evaluation tests, six minute walk test and stair climbing test were performed in 51 patients who underwent thoracoscopic sympathectomy in preoperative, first day, seventh day, thirtieth postoperative day and one year after surgery, as well as evaluation of pain and application of perceived Borg effort. Results: Spirometry showed a decrease of values around 50% in the first postoperative day, remaining still below normal values until the seventh postoperative day. The manovacuometry had reduced values only in the first postoperative day. Exercise tests showed alterations only in the first postoperative day. However, the chronotropic response as measured by pulse rate at rest and after stress tests showed significant drop right at the first postoperative day and gradually fall to the evaluation one year after the Conclusion: The thoracoscopic sympathectomy promotes procedure. immediate changes in cardiopulmonary function that are more pronounced until the 1st week, which have repercussions in the worst performance during the stress tests, but disappear within one month after surgery, suggesting that the videothoracoscopy mechanical changes is the most important factors for the fall of the evaluated parameters. Late there is a drop in baseline pulse frequency and pulse response after stress tests, but not in the performance thereof. Such changes can be attributed to sympathetic denervation, but showed no clinical repercussions in the sample investigated.